Meningkatkan Hasil Belajar Kognitif Bahasa Arab Melalui Cooperative Learning Tipe Tebak Kata - Rin-Rin Rosmayanti; Nanang Kosim (Al-Aulad: Journal of Islamic Primary Education, 2018)
The purpose of this research was conducted to find out the results of the cognitive skill, especially in the subjects of Arabic language. This research analysed before and after cognitive skill using the model of cooperative learning, and identified the activites with the approach in grade III Madrasah Ibtidaiyah (MI) Nurul Huda Bandung, West Jawa, Indonesia. This research uses Classroom Action Research (CAR), that have been implemented in two cycles.  Based on the results of the data processing, obtained mean of cognitive learning skill of students before using the model of cooperative learning is 54.09 (27%).  The application of cooperative learning in cycle I gained an average rating of teacher's activities amounted to 72% and students is 67%, respectively. Furthermore, teacher and students activities in cycle II witnessed to increase dramatically, the former is 94% and later is 92%, respectively. The cognitive skill of students in MI after using cooperative learning on cycle I gained an average rating of 75 (86%), and in cycle II derived to 95 (87.7%). This indicate that model of cooperative learning is able to enhance cognitive skill of students on Arabic subject in MI Nurul Huda Bandung.